The Separation of AHF from Fibrinogen. IV - van Creveld, S; Mochtar, I. A; Pascha, C. N (Thrombosis and Haemostasis, 1966)
The anti-hemophilic factor (AHF, factor VIII) has been separated from fibrinogen by means of continous flow electrophoresis. The starting material was Cohn’s fraction I, prepared from normal human resinplasma. These fibrinogen-free products still contained proteins without AHF-activity. Part of these contaminating proteins could be extracted from fraction I by means of a 1 molar solution of epsilon amino caproic acid. The residue, principally consisting of fibrinogen and AHF, was dissolved in a triethylamine buffer and subjected to continuous flow electrophoresis. The resulting AHF-preparations were free from fibrinogen. By immuno-electrophoresis no proteins without AHF-activity could be demonstrated in these preparations.